Kinetic Study of the Effect of Heparin on the Amidase Activity of Trypsin, Plasmin and Urokinase - Yomtova, V M; Stambolieva, N A; Blagoev, B M (Thrombosis and Haemostasis, 1983)
It was found that the effect of heparin on the amidase activity of urokinase (E C 3.4.21.31), plasmin (E C 3.4.21.7) and trypsin (E C 3.4.21.4) depended on the substrate used. No effect of heparin on the amidase activity of urokinase and trypsin was observed when Pyro Glu-Gly-Arg-p-nitroanilide (S-2444) and α-N-acetyl-L-lysine-p-nitroanilide (ALNA) were used as substrates. Heparin acted as a uncompetitive inhibitor of trypsin (Ki = 1.2×10-6 M), plasmin (Ki = 4.9×10-6 M) and urokinase (Ki = l.0×10-7 M) when Bz-Phe-Val-Arg-p-nitroanilide (S-2160), H-D-Val-Leu-Lys-p-nitroanilide (S-2251) and plasminogen, respectively, were used as substrates. These results, as well as the data obtained by studying the effect of the simultaneous presence of heparin and competitive inhibitors suggest that although heparin is not bound at the active center of these enzymes, it may influence the effectivity of catalysis.
Keywords: Uncompetitive inhibition; Heparin; Amidase activity; Trypsin-plasmin-urokinase